Dimensions of diplomacy - Bundy, McGeorge......[et al] (Baltimore, 1964)
IN 1943, under the leadership of Christian A. Herter, the School of Advanced International Studies was established in order to pro vide, in the nation's capital, a graduate institution for the training of young people in the increasingly important field of world affairs. Seven years later the School became an integral part of the The Johns Hopkins University. In the summer of 1963 SAIS moved into its new building at 1740 Massachusetts Avenue in Washington, D.C. This volume of lectures delivered during the academic year 1963-64 consequently marks not only the twentieth anniversary of the founding of SAIS but also the formal dedication of our new quarters.
Keywords: Diplomacy